Mortality and Hospitalization Risk Following Oral Androgen Signaling Inhibitors Among Men with Advanced Prostate Cancer by Pre-existing Cardiovascular Comorbidities - Lu-Yao, Grace (Eur Urol, 2019)
BACKGROUND: Elderly patients (≥65 yr) with advanced prostate cancer and cardiovascular disease (CVD) conditions are often excluded from clinical trials of abiraterone acetate (AA) or enzalutamide (ENZ). Consequently, little is known about the effects of these medications on these vulnerable patients. OBJECTIVE: To assess the short-term outcomes of AA and ENZ in patients with pre-existing CVDs. DESIGN, SETTING, AND PARTICIPANTS: A population-based retrospective study. The Surveillance, Epidemiology, and End Results-Medicare-linked database was used to identify prostate cancer patients using AA or ENZ. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: The primary endpoint was 6-mo all-cause mortality, analyzed using modified Poisson regression modeling of relative risk (RR) adjusted for confounders and comorbidities. RESULTS AND LIMITATIONS: Among eligible patients (2845 with AA and 1031 with ENZ), 67% had at least one pre-existing CVD. Compared with those without pre-existing CVDs, having one to two pre-existing CVDs was associated with 16% higher 6-mo mortality (RR = 1.16, 95% confidence interval [CI]: 1.00–1.36), and the risk increased further among those having three or more CVDs (RR = 1.56, 95% CI: 1.29–1.88). Most of the differences in survival of patients with pre-existing CVD condition occurred within the first 6 mo of treatment. CONCLUSIONS: After treatment with AA or ENZ, elderly prostate cancer patients with pre-existing CVDs experienced higher short-term mortality than otherwise similar patients without CVDs. Mortality associated with CVDs did not depend on having received AA versus ENZ. PATIENT SUMMARY: Patients with pre-existing cardiovascular diseases (CVDs) experienced higher short-term mortality after abiraterone acetate or enzalutamide than those without pre-existing CVDs. It is recommended that a multidisciplinary team, including a cardiologist, evaluate patients having pre-existing CVDs in the process of making treatment decisions and monitoring potential side effects.